Eschatological Symbolism in the Bersih Desa Ritual of Javanese Culture: A Contextual Theological Study - Wiwin Wiwin; Sefrianus Juhani; Moses Sunlety (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
In an era marked by modernization, traditional rituals are often dismissed as obsolete or merely symbolic remnants of the past. This study challenges such assumptions by exploring Bersih Desa, a Javanese communal cleansing ritual, as a site of implicit eschatological expression. Far from being a purely cultural celebration, Bersih Desa embodies the community’s deeply held hopes for spiritual continuity and post-mortem well-being. Through an ethnographic study conducted in Sumberandong hamlet, Sumberoto village, situated in the southern region of Malang Regency, this research investigates how local conceptions of the afterlife are embedded within ritual practices and communal narratives. Drawing on in-depth interviews with ritual leaders and participants, and employing Creswell’s qualitative analysis framework, the findings reveal a rich interplay between indigenous spiritual cosmologies and formal religious teachings. This syncretic understanding sustains the ritual’s vitality, functioning as a localized eschatology bridging tradition and transcendence. The study contributes to contextual theology and the anthropology of religion, offering insight into how rituals like Bersih Desa articulate the hopes and horizons of a living tradition. Practically, this study recommends that local churches embrace Bersih Desa as an inculturated locus theologicus, fostering a transformative dialogue that honors indigenous ecological spirituality while recontextualizing Christian eschatological hope within the community.